If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -6 + 4n = 0 Reorder the terms: -6 + n + 4n = 0 Combine like terms: n + 4n = 5n -6 + 5n = 0 Solving -6 + 5n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5n = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 5n = 0 + 6 5n = 0 + 6 Combine like terms: 0 + 6 = 6 5n = 6 Divide each side by '5'. n = 1.2 Simplifying n = 1.2
| 4x+7(4x-18)=162 | | -24/-3= | | 6=5x | | 7=10x | | 3x-26=19-2x | | 5x+x=90 | | 8-r=15 | | x^2+6x-9= | | 2m+4m-3m^2= | | 4(2x+5)=3(3x-5)-31 | | 18/12= | | 7(x+5)=-25+2x | | 6x+5x=90 | | 3n+26+2n+37+4n+15=180 | | (2x+9)(4x-3)=8x^2-12 | | -4x+3=83 | | 3x-7+x=21 | | -4+3=83 | | 3/4=2 | | -32/4= | | 7(y-1)=49+5y | | -3=-2+1x | | 2x-7+5x=49 | | x+7+2x+53=180 | | 12n-9+62-3n+16n+2=180 | | -32/3= | | 6y=12x-12 | | 7x+8+3x-1+4x+5=180 | | -2(3x+5)=x-52 | | 3u^2-7u-6=0 | | 2(a-4)=2a-8 | | 39=-x |